Team psychological safety and team learning: a cultural perspective. Issue 6 (12th September 2016) - Cauwelier, Peter; Ribière, Vincent M.; Bennet, Alex
Abstract : Purpose: The purpose of this paper was to evaluate if the concept of team psychological safety, a key driver of team learning and originally studied in the West, can be applied in teams from different national cultures. The model originally validated for teams in the West is applied to teams in Thailand to evaluate its validity, and the views team members have on the antecedents of team psychological safety are analyzed. Design/methodology/approach: The core of the sequential explanatory mixed method research was an experiment with nine teams from a single engineering organization (three teams from each the USA, France and Thailand). Team learning behaviors were analyzed from the conversations between team members. Team psychological safety was analyzed through a quantitative instrument and one-on-one structured interviews with each team member. Findings: The results showed that the original model is confirmed for the teams from the USA and France but not confirmed for teams from Thailand. The thematic analysis of the one-on-one interviews highlights important differences between teams from the USA and France on the one hand and teams from Thailand on the other hand when it comes to the role of the team manager and the views that team members have on the diversity between them. Originality/value: This research confirms that the concept of team psychological safety, and its impact on the way teams learn, needs to be adjusted if it is to be applied to teams in countries with national cultures different from those prevalent in the West. The implications are that researchers who develop theories in the social sciences field should evaluate how cultural differences impact their models, and that managers who implement learning and solutions should take national cultural differences into consideration.